Narrative, interaction, or both - Blommaert, Jan (Discourse Studies, 2007)
These comments focus on issues of genre in transcription formats. Bucholtz's paper takes conversation to be the a priori organizational genre of everyday talk, following a long line of interactional and conversational studies. Narrative, however, could as well be seen as an a priori genre for the organization of interaction, and many instances of talk would reflect polygeneric blending. This form of blending should be reflected in transcription practices, so that we can do justice to variation in talk by means of variation in transcription procedures.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNDYxNDQ1NjA3MDgyNTgz